Serum alpha-fetoprotein response as a preoperative prognostic indicator in unresectable hepatocellular carcinoma with salvage hepatectomy following conversion therapy: a multicenter retrospective study - Lin, Kong-Ying; Zhang, Jian-Xi; Lin, Zhi-Wen; Chen, Qing-Jing; Luo, Liu-Ping; Chen, Jin-Hong; Wang, Kui; Tai, Sheng; Zhang, Zhi-Bo; Wang, Shi-Feng; Li, Jing-Dong; Wang, Kai; et al. (Frontiers in Immunology, 2024)
Background: This study evaluates the efficacy of alpha-fetoprotein (AFP) response as a surrogate marker for determining recurrence-free survival (RFS) in patients with unresectable hepatocellular carcinoma (uHCC) who undergo salvage hepatectomy following conversion therapy with tyrosine kinase inhibitor (TKI) and anti-PD-1 antibody-based regimen.Methods: This multicenter retrospective study included 74 patients with uHCC and positive AFP (>20 ng/mL) at diagnosis, who underwent salvage hepatectomy after treatment with TKIs and anti-PD-1 antibody-based regimens. The association between AFP response-defined as a ≥ 80% decrease in final AFP levels before salvage hepatectomy from diagnosis-and RFS post-hepatectomy was investigated.Results: AFP responders demonstrated significantly better postoperative RFS compared to non-responders (P<0.001). The median RFS was not reached for AFP responders, with 1-year and 2-year RFS rates of 81.3% and 70.8%, respectively. In contrast, AFP non-responders had a median RFS of 7.43 months, with 1-year and 2-year RFS rates at 37.1% and 37.1%, respectively.Multivariate Cox regression analysis identified AFP response as an independent predictor of RFS.Integrating AFP response with radiologic tumor response facilitated further stratification of patients into distinct risk categories: those with radiologic remission experienced the most favorable RFS, followed by patients with partial response/stable disease and AFP response, and the least favorable RFS among patients with partial response/stable disease but without AFP response. Sensitivity analyses further confirmed the association between AFP response and improved RFS across various cutoff values and in patients with AFP ≥ 200 ng/mL at diagnosis (all P<0.05).The "20-80" rule based on AFP response could be helpful for clinicians to preoperatively stratify the risk of patients undergoing salvage hepatectomy, enabling identification and management of those unlikely to benefit from this procedure.